2017
DOI: 10.1002/cpp.2107
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical intrusive thoughts between obsessive–compulsive disorder, generalized anxiety disorder, and hypochondria

Abstract: Differences and similarities between intrusive thoughts typical of obsessive-compulsive disorder, generalized anxiety disorder, and hypochondriasis are relevant for their differential diagnosis, formulation, and psychological treatment. Previous research in non-clinical samples pointed out the relevance of some process variables, such as responsibility, guilt, or neutralization strategies. This research is aimed to investigate the differences and similarities between clinical obsessions, worries, and illness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…The findings showed that more than half of the non‐clinical community participants had experienced illness‐ITs in the past three months, although their frequency was generally low (‘occasionally’). Nonetheless, it was noteworthy that the reported frequency was identical to what was observed for intrusive thoughts with obsessional contents in community samples (Belloch, Roncero, & Perpiñá, 2016), which supports the notion that intrusive thoughts can be viewed as transdiagnostic variables and might be considered vulnerability factors in different disorders (Belloch, 2012; Pascual‐Vera & Belloch, 2018a; Pascual‐Vera, Roncero, & Belloch, 2017; Romero‐Sanchiz et al , 2017).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The findings showed that more than half of the non‐clinical community participants had experienced illness‐ITs in the past three months, although their frequency was generally low (‘occasionally’). Nonetheless, it was noteworthy that the reported frequency was identical to what was observed for intrusive thoughts with obsessional contents in community samples (Belloch, Roncero, & Perpiñá, 2016), which supports the notion that intrusive thoughts can be viewed as transdiagnostic variables and might be considered vulnerability factors in different disorders (Belloch, 2012; Pascual‐Vera & Belloch, 2018a; Pascual‐Vera, Roncero, & Belloch, 2017; Romero‐Sanchiz et al , 2017).…”
Section: Discussionsupporting
confidence: 70%
“…For instance, some authors have reported that patients with IAD experience intrusive imagery about their health based on memories of an earlier event, and that the contents of these intrusions primarily refer to potential health threats and feared consequences of having medical problems (Muse, McManus, Hackmann, Williams, & Williams, 2010; Wells & Hackmann, 1993). More recently, Romero‐Sanchiz, Nogueira, Godoy, Gavino, and Freeston (2017) compared the similarities and differences among worries, obsessions, and illness intrusions in terms of the appraisals, emotions, and neutralizing strategies that these cognitive products instigate in patients with obsessive–compulsive disorder (OCD), hypochondriasis, and generalized anxiety disorder (GAD). Results showed that patients with OCD scored higher on responsibility and disapproval appraisals, egodystonicity, guilt, and their use of neutralizing strategies than patients with IAD and GAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, obsession is a prerequisite for compulsion. 23 Clinically, we found that the majority of patients feared washing their faces, brushing their teeth, eating, and drinking because of severe pain. This psychological fear was found to affect patients' lives and to take up a lot of their time, severely reducing their quality of life.…”
Section: Discussionmentioning
confidence: 84%
“…In this regard, several studies and clinical observations have suggested the central role of guilt in the emergence and maintenance of OCD [13,14]. Additionally, dysfunctional metacognitive beliefs [15], obsession-related dysfunctional beliefs [16], and thought control strategies are among the factors involved in the development and persistence of OCD [17,18]. Furthermore, some studies suggest that changing dysfunctional beliefs associated with obsessions and compulsions is a suitable predictor of therapeutic changes and needs to be considered in interventions [16].…”
Section: Introductionmentioning
confidence: 99%